Perspectives on the nine symphonies of Anton Bruckner : aspects of thematic and harmonic compositional techniques, with special reference to the first and final movements, symphonies one to nine - Gibson, Penelope Anne (Rhodes University, Faculty of Humanities, Department of Music, 1982)
Preface: This thesis presents perspectives on Bruckner's compositional approach with regard to theme and harmony in the first and final movements of his symphonies one to nine. It must be realised that a fully systematic and comprehensive discussion along these lines would run into volumes. So, salient examples and common tendencies have been extracted as representative of the overall approach. However, Bruckner being the composer he is, is not dogmatic in his approach to composition and so the reader must at all times see for himself how the general technique is adapted to the individual usage in those parts not referred to in this thesis. The thesis presents the subject features of the expositions, first movements, as these are found in various adaptations in all other movements: it also aims to present a comparative study of the structural tonal principles of the works, showing how these influence the thematic forms. Whenever necessary, in the text, definitions are repeated in their original format to avoid cumbersome cross references. The most immediate source is the scores themselves, issued by the International Bruckner Society of Vienna, compiled by Dr. Leopold Nowak. All the analysis is based on these editions except for the third symphony which is based on the 2. Edition of 1878 (Wiesbaden G.M.B .H.)
Keywords: Bruckner, Anton, 1824-1896 -- Symphonies